Answer:
4x² -29x +51
Step-by-step explanation:
Put x-3 where x is in the original function definition, then "simplify". I think you'll find it convenient to rewrite the original function definition first.
... g(x) = 4x² -5x = x(4x -5)
Substituting, we have
... g(x-3) = (x -3)(4(x -3) -5)
... = (x -3)(4x -17) . . . . . simplify right factor
... = 4x² -12x -17x +51
... g(x -3) = 4x² -29x +51
To find the x-intercepts algebraically, we let y = 0 y=0 y=0 in the equation and then solve for values of x. In the same manner, to find for y-intercepts algebraically, we let x = 0 x=0 x=0 in the equation and then solve for y.
Answer:
All of the following are rational except 3.14159...
Step-by-step explanation:
Step-by-step explanation:
30 minutes x an hour and half past prolly around 1 hr and 30 sec
Answer:
-45
Step-by-step explanation:
Solve for x by simplifying both sides of the equation, then isolating the variable.